Ḥamāsahʹhā-yi millat bi-rahbarī-i Imām Khumaynī : taẓāhurāt, mubārizat...va judāgānah ḥavādi̲s-i 52 shahr az shahrʹhā-yi Īrān - Fawzī, Valī Allāh (Chāpkhānah-i ʻIlmīyah, 1980)
Chronology of the 1979 Iranian revolution and Ayatollah Khomeini's activities in and outside Iran.